Development and pilot testing of a tool to assess evidence-based practice skills among French general practitioners - Rousselot, Nicolas (BMC Med Educ, 2018)
BACKGROUND: There is currently an absence of valid and relevant instruments to evaluate how Evidence-based Practice (EBP) training improves, beyond knowledge, physicians’ skills. Our aim was to develop and test a tool to assess physicians’ EBP skills. METHODS: The tool we developed includes four parts to assess the necessary skills for applying EBP steps: clinical question formulation; literature search; critical appraisal of literature; synthesis and decision making. We evaluated content and face validity, then tested applicability of the tool and whether external observers could reliably use it to assess acquired skills. We estimated Kappa coefficients to measure concordance between raters. RESULTS: Twelve general practice (GP) residents and eleven GP teachers from the University of Bordeaux, France, were asked to: formulate four clinical questions (diagnostic, prognosis, treatment, and aetiology) from a proposed clinical vignette, find articles or guidelines to answer four relevant provided questions, analyse an original article answering one of these questions, synthesize knowledge from provided synopses, and decide about the four clinical questions. Concordance between two external raters was excellent for their assessment of participants’ appraisal of the significance of article results (K = 0.83), and good for assessment of the formulation of a diagnostic question (K = 0.76), PubMed/Medline (K = 0.71) or guideline (K = 0.67) search, and of appraisal of methodological validity of articles (K = 0.68). CONCLUSIONS: Our tool allows an in-depth analysis of EBP skills, thus could supplement existing instruments focused on knowledge or specific EBP step. The actual usefulness of such tools to improve care and population health remains to be evaluated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12909-018-1368-y) contains supplementary material, which is available to authorized users.